Letter from Harrison Shull to Robert S. Mulliken, 1960 - Shull, Harrison (1960)
Letter between Harrison Shull and Robert S. Mulliken, American quantum chemists, concerning several lectures given and planned by Mulliken, including the G. N. Lewis Medal address and the Baker lecture.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Nobel Prize winners